Breastfeeding practices, complementary feeding and nutritional status through anthropometric and biochemical indicators among preschoolers. A comparison with national health indicators - Guzmán-Mora, Alfredo (2024)
Objective: To learn about and compare breastfeeding practices, complementary feeding and the nutritional status of preschoolers attending various child development centers in a municipality of Mexico City. Materials and methods: An analytical cross-sectional study which analyzed a sample of 444 preschoolers who underwent anthropometric measurements and hemoglobin determination. Additionally, information on breastfeeding andcomplementary feeding practices was gathered from mothers. The children were categorized into two age groups (13 to 59 months and 13 to 80 months). Results: The average age was 48.4 months, with 90 % having received breastfeeding for an average of 7.7 months and 63 % having started complementary feeding before six months of age. Significant linear correlations were observed inheight-for-age (r = 0.88) and weight-for-age (r = 0.72), and 6.5 % exhibited stunting. According to the nutritional status by body mass index-for-age (BMI-for-age), 3.8 % were classified as underweight, 66.0 % as normal weight, 22.4 % as overweight and 7.8 % as obese. The distribution of these categories was consistent across genders (p = 0.90). Moreover,13.0 % were classified as at risk of malnutrition based on upper arm circumference. Girls exhibited higher percentages of body fat (BF) (p = 0.008) and total fat (TF) (p = 0.01); 4 % of the children presented anemia, being more prevalent in girls (p = 0.02). There was an average annual weight gain of 2.3 kg across age categories, except for those over six years old,who averaged 11.36 kg. Conclusions: Malnutrition is a growing public health problem. Preschool age is the ideal stage to carry out interventionsthat stimulate and promote healthy dietary habits and physical activity. Prolonged exclusive breastfeeding for at least six months is crucial for newborns and infants. In conclusion, it is imperative to refrain from using breastmilk substitutes andto delay the introduction of complementary feeding before this period.